P91 Acceptability and feasibility of measuring blood eosinophils using a point-of-care device in children with asthma. (11th November 2022) - Pavlou, B; Scotney, E; Makariou, I; Bingham, Y; Jamalzadeh, A; Hall, P; Jackman, C; Bush, A; Sonnappa, S; Fleming, L; Saglani, S
Abstract : Introduction and Objectives: Adult studies suggest that exhaled nitric oxide (FeNO) and blood eosinophils may be additive in guiding asthma management and predicting attacks. 1 Repeated venepuncture in children is challenging. We therefore aimed to assess if a finger-prick test to measure blood eosinophils using a point-of-care (POC) device is feasible and acceptable in children with asthma and assessed whether blood eosinophils correlate with contemporaneous clinical parameters. Methods: A pilot observational study, including children aged 6–16 years attending Royal Brompton Hospital with a diagnosis of asthma and prescribed maintenance inhaled corticosteroids (ICS). A capillary blood sample was obtained using a microcuvette and analysed by a HemoCue POC device to measure blood eosinophils. Finger-prick test acceptability for children and their parents/carers was assessed using a System Usability scale. The relationships between blood eosinophils and clinical parameters were analysed using Spearman's correlation and differences in blood eosinophil counts between groups using Mann-Whitney test. Results: Of 74 children approached (median age 13[range, 7–16] years), 54 were recruited, 20/74 (27%) children refused a finger-prick mostly due to being scared. The median prescribed ICS dose was 550 mcg/day budesonide equivalent (range, 100–2000 micrograms/day). The median blood eosinophil count was 0.3x10 9 L (range, 0.0–3.8x10 9 /L). All parents/carers agreed that the finger-prick test was acceptable; 45/48 (94%) of children found the test acceptable and 44/48 (92%) said it would be acceptable to have it done routinely. No correlation was found between blood eosinophils and FeNO, symptoms (asthma control test), forced expiratory volume in 1 second (FEV1 )%predicted, forced vital capacity (FVC)%predicted, or FEV1 :FVC ratio. 25/39 (64%) children had concordant blood eosinophils and FeNO, 14/39 (36%) were discordant ( figure 1 ). No relationship was found between blood eosinophil counts and the child's atopic status, sex, ethnicity or asthma control. Conclusion: Finger-prick tests are acceptable and feasible in school-aged children in an asthma clinic as a repeatable measure of blood eosinophils. Future studies should investigate the role of longitudinal eosinophil counts and their utility in predicting asthma attacks as an additional biomarker combined with spirometry and FeNO. References: Couillard S, et al. Thorax 2021;77 :199–202